2005
DOI: 10.3200/genp.132.3.313-320
|View full text |Cite
|
Sign up to set email alerts
|

Fox Urine as an Aversive Stimulus: Modification of a Passive Avoidance Task

Abstract: Predator urine, specifically fox urine, is a noxious but harmless olfactory stimulus. The results of previous studies have shown that fox urine is aversive to rats, and that rats react to fox urine in a similar manner as to other psychostressors. In the present study, the authors further investigated the use of fox urine as an aversive or stressful stimulus, specifically examining behavior change in open-field place-preference task. Three methods of presenting the fox urine were examined. Results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
(6 reference statements)
1
3
1
Order By: Relevance
“…As predicted, Prkar1a +/- mice failed to exhibit behavioral changes (exploratory or defensive) to distinguish between predator versus control odor exposure, which was an effect of the genotype. The behavioral response of the WT mice confirmed prior findings of laboratory and field studies that exposure to predator odor would reduce exploratory and non-defensive behaviors (Blanchard and Blanchard, 1989; Farmer-Dougan et al, 2005; Dielenberg et al, 2001a), thus providing an important control for this study Therefore, the behavioral response of Prkar1a +/- mice is consistent with the “prediction error” hypothesis of anxiety disorders, specifically a deficit in the ability to discriminate between an ambiguous versus a predator threat.…”
Section: Discussionsupporting
confidence: 83%
“…As predicted, Prkar1a +/- mice failed to exhibit behavioral changes (exploratory or defensive) to distinguish between predator versus control odor exposure, which was an effect of the genotype. The behavioral response of the WT mice confirmed prior findings of laboratory and field studies that exposure to predator odor would reduce exploratory and non-defensive behaviors (Blanchard and Blanchard, 1989; Farmer-Dougan et al, 2005; Dielenberg et al, 2001a), thus providing an important control for this study Therefore, the behavioral response of Prkar1a +/- mice is consistent with the “prediction error” hypothesis of anxiety disorders, specifically a deficit in the ability to discriminate between an ambiguous versus a predator threat.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, TMT induced a significant increase in immobility, one of the most prominent behavioural effects of TMT 24 , 40 . Surprisingly, exposure to fox urine did not induce overt defensive behaviour in the present experiment, although this has been shown in previous studies of our group 20 , 41 44 and of others 45 – 47 . A potential reason for this may be that the experimental protocol of the present study differed from the one used before.…”
Section: Discussioncontrasting
confidence: 78%
“…Similar effects have been shown in a number of studies with other prey species: beavers, black-tailed deer, snowshoe hares, deer mice, guinea pigs, house mice, gray squirrels, meadow voles, and mountain voles during exposure to coyote, wolf, fox, and bobcat urine (Sullivan et al, 1985a(Sullivan et al, ,b, 1988Epple et al, 1993;Nolte et al, 1994;Swihart et al, 1999;Rosell, 2001), and, most relevantly, in rats during exposure to fox urine (Burwash et al, 1998;Campbell et al, 2003;Farmer-Dougan et al, 2005). The results of all these studies were confirmed here.…”
Section: Discussionmentioning
confidence: 56%